2018
DOI: 10.3390/su10103805
|View full text |Cite
|
Sign up to set email alerts
|

Paradigm Found? Immanent Critique to Tackle Interdisciplinarity and Normativity in Science for Sustainable Development

Abstract: The ambition of this two-part article is to argue for immanent critique as a research strategy in sustainability studies. We do this by picking up and developing two central, cross-cutting themes in sustainability research, namely interdisciplinarity and normativity. It is widely suggested that the problem-driven and solution-focused orientation in sustainability studies necessitates interdisciplinarity and an engagement with questions of normativity, each creating problems regarding how science is conducted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 88 publications
0
52
0
1
Order By: Relevance
“…In the following sections, we examine theoretical limitations and tensions within and between different perspectives, and how they might be complementary, inspired by the method of immanent critique [80] and Lakatos idea of progressive and degenerative research programmes [81]. For meaningful exchange across disciplinary boundaries, we consider complementary among the perspectives a condition.…”
Section: Discussion: the Possibilities And Limitations Of An Integratmentioning
confidence: 99%
See 3 more Smart Citations
“…In the following sections, we examine theoretical limitations and tensions within and between different perspectives, and how they might be complementary, inspired by the method of immanent critique [80] and Lakatos idea of progressive and degenerative research programmes [81]. For meaningful exchange across disciplinary boundaries, we consider complementary among the perspectives a condition.…”
Section: Discussion: the Possibilities And Limitations Of An Integratmentioning
confidence: 99%
“…It can be achieved by either aligning theories with auxiliary hypotheses, or, where that is not possible, sublating more foundational tensions with a new synthesis that reconcile contradictory conceptions. It has been suggested that one procedural logic for doing so is that of immanent critique [80]. At its most basic, immanent critique is a method for identifying limitations and contradictions within a perspective and suggesting what might resolve them.…”
Section: Not Easily Compatiblementioning
confidence: 99%
See 2 more Smart Citations
“…This then provided a platform for working with management practitioners to formulate more adequate goals and practices for the city. These systematically arose from attempts to correct the theoretical and practical tensions uncovered in the analysis of current goals and practices (for more on the methodology of immanent critique, see Boda and Faran 2018). Throughout the research process, a range of methods was used to generate primary and secondary data related to the socio-cultural, economic, and bio-physical characteristics of the case.…”
Section: Study Areamentioning
confidence: 99%